Case Report: Uroenteric Fistula in a Pediatric-en-bloc Kidney Transplant Manifests as Deceptive Watery Diarrhea and Normal Anion Gap Acidosis - Al Barbandi, Malek; Defreitas, Marissa J.; Infante, Juan C.; Morsi, Mahmoud; Arroyo Parejo Drayer, Patricia A.; Katsoufis, Chryso P.; Seeherunvong, Wacharee; Chandar, Jayanthi; Burke, George W.; Abitbol, Carolyn L. (Frontiers in Pediatrics, 2021)
Introduction: The diagnosis of a post–surgical uroenteric fistula can be challenging and may be delayed for months after symptoms begin. A normal anion gap metabolic acidosis has been reported in up to 100% of patients after ureterosigmoidostomy, and bladder substitution using small bowel and/or colonic segments. Here, we describe a rare case of a pediatric patient who developed a uroenteric fistula from the transplant ureters into the small bowel, after an en-bloc kidney transplantation resulting in profound acidosis and deceptive watery diarrhea. Case Presentation: The patient is an 8-year-old girl with end stage kidney disease (ESKD) secondary to focal segmental glomerulosclerosis. Through a right retroperitoneal approach, she underwent a right native nephrectomy and a pediatric deceased donor en-bloc kidney transplant including two separate ureters. One month later, she had a renal allograft biopsy for suspected rejection. During the week after the biopsy, she experienced abdominal pain followed by watery diarrhea and metabolic acidosis requiring continuous bicarbonate/acetate infusions. An extensive gastro-intestinal evaluation for the cause of the diarrhea including endoscopy was inconclusive. The urine output decreased to less than 500 ml daily; although, the kidney function remained normal. After 2 weeks of unexplained watery diarrhea a magnetic resonance urogram with contrast was performed which demonstrated extravasation of urine from both ureters with fistulization into the small bowel. She underwent corrective surgery which identified the fistulous tract, which was resected and both ureters were re-implanted. The diarrhea and acidosis resolved, and she has maintained normal renal allograft function for over 1 year. Conclusion: An important aspect in the early diagnosis of a uroenteric fistula is the sudden onset of severe hyperchloremic metabolic acidosis that results when urine is diverted into the intestinal tract. The mechanism is similar to that described in cases of urinary diversions and/or bladder augmentation using the intestine. Important diagnostic tools are the measurements of solute excretion and pH in the urine as compared to the “watery diarrhea” or bowel output.